PREPARATION AND EVALUATION OF DROTAVERINE HCL ORAL DISINTEGRATING TABLETS USING SOLID MIXTURE TECHNIQUE - Hari, Kuralla; Rajeswari, Saripilli; Ramana Murthy, Kolapalli Venkata (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to formulate orally disintegrating taste masked tablets of drotaverine HCl using solid mixture technique. Methods: Taste masked drug-polymer solid mixtures of drotaverine HCl were prepared by using hydroxypropyl methylcellulose (HPMC) 3 cps and rxcipientÂ® FM1000/calcium silicate (rxcipient) as carriers employing kneading method using varying drug-polymer ratios of 1:1, 1:5, 1:7.5, and 1:9. Prepared drug-polymer mixtures evaluated for taste masking, and the ratio of drug-polymer is optimized. The granules and tablets prepared with optimized drug-polymer ratio were evaluated for pre- and post-compression parameters, in vitro dissolution studies, Fourier-transformation infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffractometry (XRD) studies. Results: The drug:polymer ratios 1:7.5 with rxcipient and 1:9 with HPMC were optimized based on taste evaluation. The pre-compression results showed that all the formulae have good flow properties. The post-compression evaluations showed that all the formulae met the specifications of orally disintegrating tablets. From all the prepared taste masked drotaverine HCl tablets, R10 formulation consisting of 4% croscarmellose sodium and H9 formulation consisting of 3% croscarmellose sodium, 3% sodium starch glycolate, and 2% microcrystalline cellulose shown more than 99% drug release in 60 min, and both the formulations showed better taste masking and were meting oral disintegrating tablet (ODT) parameters. The optimized formulation was characterized by FTIR, DSC, and XRD studies and found no incompatibility. Conclusion: The results demonstrated that the prepared drotaverine HCl ODT showed better taste masking and meeting the parameters of ODT formulations R10 and H9. The present solid mixture technique can be effectively used for taste masking.